PENGARUH KUALITAS PEMBIAYAAN TERHADAP EFEKTIVITAS PENDAPATAN (Studi Kasus di BMT Artha Barokah Yogyakarta 2012) - Amrizal Putra; Ahmad Yunadi (Universitas Alma Ata, 2015)
Abstract KJKS BMT is an institution that serves as an intermediary (Intermediary Institution) ﬁ nancial, KJKS BMT third -party funds to the public. Among them are mudharabah and Musharaka. The background of this research is that the prospects of the business, customer performance, and the ability to pay is a factor that is used to measure the effectiveness of customer revenue Artha Barokah BMT. This study was conducted to determine whether the business prospect, customer performance, and the ability to pay affect the revenues of the BMT Artha Barokah customers. Type of research is a ﬁ eld (ﬁ eld reserch) with documentation of data collection methods, because the data used in this study is secondary data obtained from the customer data is ﬁ lled directly. The analytical tool used is multiple linear regression testing using classical linear regression aberration test and statistical tests . Results of t test analysis showed that each of the independent variables signiﬁ cantly affect the revenues of customers in BMT Artha Yogyakarta blessing . In the F test shows that the performance of the independent variables and the ability of customers to pay a signiﬁ cant effect while the prospects do not signiﬁ cantly inﬂ uence customers’ budget revenues. The determinansi coefﬁ cient ( R ² ) of 0.440 , which means that the budget revenue on customer BMT Artha Barokah able to be explained by the independent variables was 44.0 % and the remaining 56.0 % is inﬂ uenced by other variables outside the model of this study Keywords: BMT, Financing Quality, The Effectiveness of Income